Challenges of monitoring use of secondary care at local level: a study based in London, UK. Issue 3 (June 1996) - Chenet, L; McKee, M
Abstract : STUDY OBJECTIVE: To provide those working at district level with practical guidance on using hospital data linked to small geographic areas to explore patterns of care. DESIGN: Examination of the association between age standardised hospital episode rates for the commonest diagnostic categories and deprivation levels (Carstairs index) of the electoral ward of residence. SETTING: An inner London district, Kensington, Chelsea and Westminster, with a population of approximately 325, 000. POPULATION: All finished consultant episodes recorded in NHS hospitals for the district population in the year to April 1994. MAIN RESULTS: Many, but not all, disease categories were associated strongly with deprivation, with high episode rates in the most deprived electoral wards. This is partly due to more of those in deprived areas being admitted to hospital and to them being admitted more often. CONCLUSIONS: A wide range of factors needs to be taken into account in interpreting these data. They include the contribution of the private sector and artifacts of both the numerator and denominator. This paper provides a framework for those working at district level to begin to analyse the association between hospitalisation and deprivation locally. It also identifies some of the issues that must be taken into account when seeking to interpret these data.